1992
DOI: 10.1111/j.1438-8677.1992.tb00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Evidence of Connexin‐like Proteins in the Plasma Membrane of Vicia faba L.

Abstract: _ . _ --Plasma membranes from three week old leaves of Vicia foba L. were enriched by aqueous twophase partitioning to high purity. Plasma membrane proteins were immunoblotted with polyclonal, monospecific antibodies raised against mouse liver connexins (ex) 32 and 26. Immunostaining after treatments with ex BSA: 32 antibodies revealed the existence of a 29 kDa protein, clearly enriched in the plasma membrane fraction, An additional immunoreactive band of 20 kDa, possibly a degradation product of the 29 kDa pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
1
18
1
Order By: Relevance
“…Table 4 shows the inhibition of membrane-bound ATPase (pH 6.1) activity by various inhibitors in PMs and crude microsomes. The PM preparations showed a purity similar to that ob- in one out of three independent preparations with similar results tained with green leaves from other species (Kjellbohm and Larssen 1984;Briiggemann and Janiesch 1989;Hunte et al 1992). In the course of the preparation, NADH-dependent FCR activity increased from 3.75+0.15 (leaf crude microsomes) to 7.25+2.39 (leaf PM) nmol 9 (mg protein)-1 .…”
Section: Resultssupporting
confidence: 68%
“…Table 4 shows the inhibition of membrane-bound ATPase (pH 6.1) activity by various inhibitors in PMs and crude microsomes. The PM preparations showed a purity similar to that ob- in one out of three independent preparations with similar results tained with green leaves from other species (Kjellbohm and Larssen 1984;Briiggemann and Janiesch 1989;Hunte et al 1992). In the course of the preparation, NADH-dependent FCR activity increased from 3.75+0.15 (leaf crude microsomes) to 7.25+2.39 (leaf PM) nmol 9 (mg protein)-1 .…”
Section: Resultssupporting
confidence: 68%
“…First biochemical and molecular information on plasmodesmata came from studies demonstrating the presence of animal connexin-homologous proteins in plants [33,34,36,41,42,43,44,59,81,82]. Schindler and co-workers noted numerous functional homologies between plasmodesmata and between animal gap junctions, structures involved in cytoplasmic cell-to-cell communication in animals.…”
Section: Plasmodesmatal Compositionmentioning
confidence: 99%
“…These functional analogies included similar behavior with regard to SEL tracer dyes, similar electrical properties and similar modes of down-regulation by effectors of protein kinase C. It was suggested that there may be biochemical homologies between gap junction proteins and plasmodesmatal proteins. Immunological data suggested that dicotyledonous plants contain peptides immunologically related to the mammalian gap junction proteins, connexin32 [33,41,42,44,81], and connexin26 [33,34,59]. Indirect evidence suggested that these crossreacting proteins [33,34,59,81] may be plasmodesma-associated.…”
Section: Plasmodesmatal Compositionmentioning
confidence: 99%
See 2 more Smart Citations